DIGITAL DA’WAH AND SOCIAL STRATIFICATION IN SOCIETY 5.0 - Nakhlah Faridah Ash Sholichah; Bintang Mahesa Jenar; Rofiqotul Nikmatil Uliyah; Ali Hasan Siswanto (CV. ADIBA AISHA AMIRA, 2025)
This article examines the intersection between digital social stratification and contemporary da’wah practices in the era of Society 5.0. Through a critical literature review and comparative qualitative approach, this study integrates classical stratification theory with insights from digital sociology and Islamic communication. The findings demonstrate that disparities in technological access, digital literacy, device quality, and algorithmic visibility generate new layers of inequality that shape Muslims’ ability to access, interpret, and participate in online da’wah. At the same time, digital platforms open opportunities for horizontal mobility, participatory religious engagement, and wider dissemination of Islamic knowledge beyond traditional boundaries. The study argues that reconstructing da’wah in the digital age requires inclusive digital strategies, literacy empowerment, and ethical communication frameworks to promote justice, equity, and meaningful religious participation. Ultimately, addressing digital inequality is essential for ensuring that da’wah in Society 5.0 contributes to inclusive Islamic social transformation.